Efficacy of bivalent vaccine against black body syndrome (BBS) of barramundi Lates calcalifer B. - Anis Nugrahawati; Sri Nuryati; Sukenda Sukenda; Rahman Rahman; Margie Brite; Tiya Widi Aditya (Jurnal Akuakultur Indonesia)
ABSTRACT